The marketing planning workbook : effective marketing for marketing managers - Dibb, Sally; Simkin, Lyndon; Bradley, John. (London : International Thomson Business Press, 1996)
This book is about: Perspective; Core analyses; Analyses into strategy-Marketing strategy summary; Programmes for implementation; The marketing planning document; ...
Keywords: Marketing; Management; Export marketing -- Management